MISTISISME POCONG SEBAGAI REPRESENTASI ARWAH GENTAYANGAN (Studi Tipologi Clifford Geertz): Indonesia - Zulkifli, Zulkifli; Fitria, Risa Pramita Wilda (Ri'ayah: Jurnal Sosial dan Keagamaan, 2023)
The pocong figure is a strong representation of the wandering spirits who have not found peace after death, so some people still believe that the posong figure is still attached to the real world and therefore can still interact with the real world itself. This study aims to analyze the mysticism of pocong as a representation of wandering spirits in Indonesian society using Clifford Geertz's typological approach. In this study, the authors apply the Geertz typology approach to interpret the meaning and role of pocong in the Indonesian cultural context. This research is qualitative with the type of library research; therefore, a literature review from books, scientific articles, magazines, and other sources is used in this research to gain an understanding regarding pocong mysticism as a representation of wandering spirits in Indonesian culture. The results of this study indicate that pocong in the context of Indonesian culture is not only a horror story or tale, but pocong in its context also plays a role in shaping people's behavior and beliefs in mystical matters after death. This research can contribute to beliefs, mystical rituals, and pocong mysticism as wandering spirits in Indonesian culture.